Experimental evaluation of recent consolidation theories using soft Rangsit clay - Karunakaran, Suppiah; Brenner, R.P.; Balasubramaniam, A.S.; Onodera, T. F.; The Government of United Kingdom (Bangkok : Asian Institute of Technology, 1977)
After reviewing and classifying consolidation theories, three recent models, namely those of Gibson & Lo, Barden and Garlanger were investigated using soft Bangkok clay from Rangsit. Samples were tested in the Bishop and Rowe type hydraulic oedometers with pore pressure measurement using four different values of load increment ratio and load increment duration and three values of sample thickness. Gibson & Lo's and Barden's parameters were evaluated from the data obtained in the secondary compression range. Both settlements and pore pressures were then generated for the whole time duration observed using the experimentally,4etermilned, values. The comparison of these generated values with the observed ones showed that the generated pore pressures did not agree for either of the two models, whereas the generated settlements gave a fairly good agreement over the whole time range for the Gibson & Lo model. For the Barden model, a reasonable agreement was only obtained in the secondary compression range. Garlanger1s parameters were obtained utilizing the experimental observations from the entire time range. In this case, parameters evaluated from step loading produced rather poor agreement with parameters obtained from a test simulating in-situ loading. Clear trends in the effect of load increment ratio, load increment duration and sample thickness on the different model parameters characterizing the three theories considered could be recognized only in a few cases.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Soil consolidation test